SEXUAL DYSFUNCTION IN PAKISTANI MARRIED WOMEN WITH CURRENT EPISODE OF DEPRESSION AND BIPOLAR: A QUALITATIVE STUDY - Yosuf, Tahira; Farhan, Sheeba (Journal of Pakistan Psychiatric Society, 2024)
The awareness of psychological disorders in the present times is increasing with the help of dynamic psychological assessment tools, advancing with progressive investigation methods. Current psychological literature significantly emphasizes on depression and bipolar disorders, their prevalence, assessment, and treatment protocols among the married individuals. Despite the increasing prevalence of depression among women, scholarly literature scarcely addresses on the impacts of sexual dysfunction on the married women in Pakistan, experiencing depression and associated bipolar disorder.The aim of this research was to study the impact of Sexual Dysfunction in Pakistani Married Women with Depression and Bipolar Disorder. A sample of 8 participants was selected with the help of purposive sampling. Each of these participants was diagnosed with depression and/or bipolar disorder and was undergoing therapy for the same. A semi-structured interview was conducted with each of these participants to deduce information about their disorders and sexual dysfunction. Thematic analysis was employed as the qualitative analysis technique for the evaluation of results gathered from interviews. The analysis revealed two main themes: Past experiences and current relationships. In the theme, experiences sub themes of parental relationships and childhood experiences were observed. Whereas in the theme Current Relationships, subthemes of the current marital relationship and current sexual relationship were observed. The themes and sub-themes revealed that married Pakistani women who are facing Depression and Bipolar Disorder, also go through sexual dysfunction.